Driving Management of Novel Foods: A Network Analysis Approach - Zarbà, Carla; Chinnici, Gaetano; Hamam, Manal; Bracco, Salvatore; Pecorino, Biagio; D'Amico, Mario (Frontiers in Sustainable Food Systems, 2022)
The food industry has confronted, in recent years, numerous issues including meeting a food demand for individual well-being in a sufficient and healthy manner, also due to the effects of the world population growth. In this scenario, alternative food sources may be a key element both for their contribution to food needs and for the promotion of sustainable and innovative production patterns. These food sources, new compared to traditional food styles, have been regulated by specific European Union regulations under the definition of novel foods. Their importance in the world has raised different topics of scientific research. The present paper aimed to seize the direction of scientific studies in the world focused on the thematic area of novel foods, from the management point of view. At the scope, this study analyzed 209 papers and carried out a descriptive analysis and a network analysis of the thematic areas under examination also with the help of the software Vosviewer. The results highlighted the importance of scientific research in the world also for the contributions on the exploration of existing markets as well as for the innovative solutions it provides, which aim to expand market possibilities. Finally, the existence of several elements and factors, that may discourage the propensity to consume and therefore the development of the novel foods market, seemed to emerge, and for this reason, many surveys focused on finding solutions to overcome these potential obstacles.